Capture, Unfolding, and Detection of Individual tRNA Molecules Using a Nanopore Device - Smith, Andrew M.; Abu-Shumays, Robin; Akeson, Mark; Bernick, David L. (Frontiers in Bioengineering and Biotechnology, 2015)
Transfer RNAs (tRNA) are the most common RNA molecules in cells and have critical roles as both translators of the genetic code and regulators of protein synthesis. As such, numerous methods have focused on studying tRNA abundance and regulation, with the most widely used methods being RNA-seq and microarrays. Though revolutionary to transcriptomics, these assays are limited by an inability to encode tRNA modifications in the requisite cDNA. These modifications are abundant in tRNA and critical to their function. Here we describe proof-of-concept experiments where individual tRNA molecules are examined as linear strands using a biological nanopore. This method utilizes an enzymatically ligated synthetic DNA adapter to concentrate tRNA at the lipid bilayer of the nanopore device and efficiently denature individual tRNA molecules as they are pulled through the α-hemolysin (α-HL) nanopore. Additionally, the DNA adapter provides a loading site for ϕ29 DNA polymerase (ϕ29 DNAP), which acts as a brake on the translocating tRNA. This increases the dwell time of adapted tRNA in the nanopore, allowing us to identify the region of the nanopore signal that is produced by the translocating tRNA itself. Using adapter-modified E. coli tRNAfMet and tRNALys, we show that the nanopore signal during controlled translocation is dependent on the identity of the tRNA. This confirms that adapter-modified tRNA can translocate end-to-end through nanopores and provides the foundation for future work in direct sequencing of individual transfer RNA with a nanopore-based device.